Pendampingan UMKM Kosmetik dengan Inovasi dan Adaptasi terhadap Tren Global melalui Platform Digital - Sari, Meci Nilam; Septrizarty, Rika; Mulyadin, Asrul; Yuliana, Sartika; Angraini, Nadia; Maliha, Dabitha Wise; Anita, Devi (Jurnal PADAMU NEGERI (Pengabdian pada Masyarakat Bidang Eksakta), 2025)
This community service initiative aims to analyze the role of mentoring for micro, small, and medium enterprises (MSMEs) in the cosmetics sector, particularly in addressing global trends through digital platforms. With the rapid advancement of technology and globalization, cosmetic MSMEs must adapt to remain relevant and competitive. The mentoring provided to cosmetic MSME entrepreneurs includes training in the use of social media, digital marketing, and product innovation to meet the demands of the global market. The results of the community service activity indicate that digitalization has had a positive impact on the competitiveness of MSMEs, enhancing entrepreneurs’ understanding of the digital market, encouraging adaptation to global trends, and ultimately improving product quality and sales performance.